2011
DOI: 10.1111/j.1462-5822.2011.01606.x
|View full text |Cite
|
Sign up to set email alerts
|

The thermolysin-like metalloproteinase and virulence factor LasB from pathogenic Pseudomonas aeruginosa induces anoikis of human vascular cells

Abstract: SummaryDisruption of cell/ECM interactions resulting from uncontrolled pericellular proteolysis leads to detachment-induced cell apoptosis (anoikis), contributing to the morbid evolution of inflammatory vascular diseases. During cardiovascular infections, bacterial proteinases might induce vascular cells to enter a similar pathway. We focused on LasB, the predominant metalloproteinase secreted by the haematotropic pathogen Pseudomonas aeruginosa. While the exosecretome of the LasBdeficient pseudomonal strain P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 76 publications
6
52
1
Order By: Relevance
“…Anoikis, a Greek word meaning loss of home or homelessness, is due to loss or inappropriate cell adhesion to ECM. Anoikis is observed both physiologically (in normal skin, in colonic epithelium, in the involuting mammillary glands), as well as in many pathologic conditions such as metastatic spreading and cardiovascular degenerative processes including VSMCs disappearance in aneurysms and varicose veins, extensive loss of vascular cells during cardiovascular infections, cardiac myocyte detachment in heart failure, and plaque rupture in atherosclerosis [4,12,27].…”
Section: Discussionmentioning
confidence: 99%
“…Anoikis, a Greek word meaning loss of home or homelessness, is due to loss or inappropriate cell adhesion to ECM. Anoikis is observed both physiologically (in normal skin, in colonic epithelium, in the involuting mammillary glands), as well as in many pathologic conditions such as metastatic spreading and cardiovascular degenerative processes including VSMCs disappearance in aneurysms and varicose veins, extensive loss of vascular cells during cardiovascular infections, cardiac myocyte detachment in heart failure, and plaque rupture in atherosclerosis [4,12,27].…”
Section: Discussionmentioning
confidence: 99%
“…Enhancement of anoikis, not compensated by cell healing or overcompensated by a dysfunctional healing process, as observed during fibrosclerosis, is probably responsible for cardiovascular degenerative pathologies, such as cardiac myocyte detachment in heart failure, plaque rupture in atherosclerosis, smooth muscle cell disappearance in aneurysms and varicose veins and extensive loss of vascular cells during cardiovascular infections [146][147][148]. Proteases able to degrade ECM proteins induce anoikis of endothelial cells or other components of the cardiovascular system, such as smooth muscle cells, fibroblasts and cardiac myocytes.…”
Section: Anoikis Induction In Cardiovascular Diseases and Diabetesmentioning
confidence: 99%
“…Beaufort and collegues have recently reported that the haematotropic pathogen Pseudomonas aeroginosa induce an intense anoikis of cardiomyocytes and valvular myofibroblasts, thus contributing to host tissue destruction [146]. In particular, the uncontrolled pericellular proteolysis responsible for extensive cell detachment mainly depends on the metalloproteinase LasB, one of the well-known proteolytic enzymes secreted by P. aeruginosa.…”
Section: Anoikis Induction In Cardiovascular Diseases and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported in a different context that the persistence of an infected thrombus in contact with the underlying tissue represents a source of blood-conveyed proteases, including both bacterial and host leukocyte proteases released upon activation (4,8). For example, neutrophil elastase has been shown to induce cell death subsequent to pericellular proteolysis and to be deleterious for vascular tissues (9,10).…”
mentioning
confidence: 99%